2006
DOI: 10.1080/00140130600665687
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of slips: an evaluation of utilized coefficient of friction and available slip resistance

Abstract: The purpose of this study was to investigate the relationship between measures of floor surface slip resistance and an individual's peak utilized coefficient of friction (COFU) on the probability of a slip occurring during level walking. Video, kinematic and ground reaction force data were recorded simultaneously as subjects walked at a self-selected speed during conditions of normal and reduced floor surface slip resistance. Peak COFU during weight acceptance was calculated and the available floor surface sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 29 publications
2
53
1
Order By: Relevance
“…4), the ratio of real contact area to normal force (A c /F N ) should be proportional to the adhesion coefficient of friction (Eqs. [3][4][5]. The A c /F N was averaged across the second loading step (Fig.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…4), the ratio of real contact area to normal force (A c /F N ) should be proportional to the adhesion coefficient of friction (Eqs. [3][4][5]. The A c /F N was averaged across the second loading step (Fig.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…According to Liberty Mutual Workplace Safety Index, fall accidents had the highest percentage of cost growth trends among the most disabling workplace injuries between 1998 and 2010 [2]. Previous research has reported an increase in the probability of slips and falls when the available coefficient & Kurt E. Beschorner beschorn@pitt.edu of friction between shoe and floor becomes less than the required coefficient of friction [3,4]. Improving friction through enhanced slip-resistant shoes and flooring designs is an effective strategy for reducing slip and fall injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Burnfield and Powers 17) set pedestrians across a lubricated force-plate, and used logistic regression to predict pedestrian slips, separately using the difference between available and utilized/required friction (as did Hanson 16) ) and just available friction as the independent variable. They determined that, while the friction difference gave the most accurate results, available friction alone also proved "accurate.…”
Section: Research Background-logistic Regressionmentioning
confidence: 99%
“…Our discussion focuses on COF measured at the start of motion (static), rather than during motion (kinetic). Slip resistance (measured as static COF) is a good predictor of slips, 26,27 with a person being less likely to fall with a higher COF. Many factors can affect friction, however, including water, sweat, dirt, oil, skin condition, and wear of the bathtub or shower floor surface.…”
Section: Figurementioning
confidence: 99%